Implementation of Simulation Methods in Leadership Value Learning - Novi Daniati (Alinea: Jurnal Bahasa, Sastra, dan Pengajaran, 2018)
This article describes the implementation of the simulation method of leadership values of Prince Pemanah Rasa in Sasakala Prabu Siliwangi by Muhammad Fajar Laksana, judging by the effectiveness of the application of methods and the students' ability in analyzing the value of leadership. The method used in this research is descriptive method with research object of class VIII E students as much as 35 people. The result of the research shows that the students of class VIII E MTs Islamiyah Sayang consider the effective simulation method used in the learning of folklore with the percentage of 97,1%. The students' ability in analyzing the leadership value of Prince Pemanah Rasa figure, 12 students (34,2%) got 80 (good category), 9 students (25,8%) got 70 (enough category), 7 students (20%) scored 60 (moderate category), and 3 students (8.6%) got the value of 40 (less category). It shows that students' ability in analyzing the leadership value of Prince Pemanah Rasa figure is enough, seen from percentage of average ability which reach 66.6%.Keywords: simulation, sasakala prabu siliwangi, leadership value